2018
DOI: 10.1002/chem.201805245
|View full text |Cite
|
Sign up to set email alerts
|

[All]‐S,S‐dioxide Oligo‐Thienylenevinylenes: Synthesis and Structural/Electronic Shapes from Their Molecular Force Fields

Abstract: Oligo‐S,S‐dioxothienylenevinylenes have been prepared by transferring oxygen atoms to the sulfur atoms using the HOF⋅CH3CN complex. Their photophysical properties are presented in comparison with their thiophenevinylene congeners. Together with their vibrational properties and molecular force fields, this study allows for the interpretation of the alteration of aromaticity and inter‐ring exocyclic π‐conjugation in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…[23][24][25] The chemical oxidation of thienyl groups to their S,S'-dioxidized analogues is another effective approach to enhance luminescence efficiency [26][27][28][29] and alter charge transport behavior from p-channel to n-channel. [30,31] So far, numerous reports on the selective or full oxidation of sulfur atoms in the electron-rich oligothiophenes [32,33] or fused-thiophene systems [30,[34][35][36] have confirmed that the sulfonylation provides a feasible option in the structural and optoelectronic modulation. Adachi and co-workers have recently made a huge advance in the field of organic electroluminescence research field by introducing purely organic molecules that can give efficient thermally activated delayed fluorescence (TADF) through upconversion of triplet to singlet states, and therefore lead to potentially 100 % internal singlet yields.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] The chemical oxidation of thienyl groups to their S,S'-dioxidized analogues is another effective approach to enhance luminescence efficiency [26][27][28][29] and alter charge transport behavior from p-channel to n-channel. [30,31] So far, numerous reports on the selective or full oxidation of sulfur atoms in the electron-rich oligothiophenes [32,33] or fused-thiophene systems [30,[34][35][36] have confirmed that the sulfonylation provides a feasible option in the structural and optoelectronic modulation. Adachi and co-workers have recently made a huge advance in the field of organic electroluminescence research field by introducing purely organic molecules that can give efficient thermally activated delayed fluorescence (TADF) through upconversion of triplet to singlet states, and therefore lead to potentially 100 % internal singlet yields.…”
Section: Introductionmentioning
confidence: 99%